Designing selective modulators for the nicotinic receptor subtypes: challenges and opportunities. (13th February 2018) - Manetti, Dina; Bellucci, Cristina; Chiaramonte, Niccolò; Dei, Silvia; Teodori, Elisabetta; Romanelli, Maria Novella
Nicotinic receptors are membrane proteins involved in several physiological processes. They are considered suitable drug targets for various CNS disorders or conditions, as shown by the large number of compounds which have entered clinical trials. In recent years, nonconventional agonists have been discovered: positive allosteric modulators, allosteric agonists, site-specific agonists and silent desensitizers are compounds able to modulate the receptor interacting at sites different from the orthodox one, or to desensitize the receptor without prior opening. While these new findings can further complicate the pharmacology of these proteins and the design and optimization of ligands, they undoubtedly offer new opportunities to find drugs for the many therapeutic indications involving nicotinic receptors.